Recent developments on encapsulation of lactic acid bacteria as potential starter culture in fermented foods – A review. (February 2018) - Kavitake, Digambar; Kandasamy, Sujatha; Devi, Palanisamy Bruntha; Shetty, Prathapkumar Halady
Abstract: Fermented foods are the first processed staple human diet that have been produced and consumed since development of human civilizations. Majority of the fermented foods are made through controlled microbial growth and enzymatic conversions of major and minor food components that gain high values because of its enhanced organoleptic properties. Ease of fermentation, risk in fermentation failure and several functional properties of lactic acid bacteria makes them as suitable starter culture in production of fermented foods. The viability and stability of starter cultures in the fermented foods and gastro intestinal environment are key challenges at industrial scale. Use of encapsulated starter cultures has been considered more in the recent years, due to its improvement in survival and viability under adverse environmental conditions. This paper mainly focuses on reviewing lactic acid bacteria as functional starter cultures in fermented foods including different techniques and coating materials used for microencapsulation, factors affecting the microencapsulation, methods for evaluating the efficiency of starter cultures and future perspectives to be overcome in this area. Highlights: Potential use of lactic acid bacteria (LAB) as starter culture in fermented foods. Detailed overview on methods, coating materials and factors affecting encapsulation. Future perspectives and challenges in encapsulation of starter culture.